One Simple Cosmological Implication of Light Transmition in Hubble’s Law - Dialynas, Thanassis (European Journal of Applied Sciences, 2023)
Hubble’s law gives a great indication that the Universe expands and will do so in the near future. In this “Paper” we try to extract information from Hubble’s law and so to retrace its forward and backward steps. The most “striking” result for the universe is that the “theory” predicts a maximum radius of the universe and a maximum life-time. In addition one can predict if there is causality in between two points (t2 ,d2 ) and (t2 ,d2 ) of space time.